2018
DOI: 10.14704/nq.2018.16.5.1415
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Research with Combination of Whole Brain Teaching and Basketball Techniques

Abstract: This paper gives exploration on the whole brain teaching of techniques and tactics by aiming at basketball teaching of middle school, and it makes analysis and discussion by conducting whole brain teaching experiment on techniques and tactics, with the expectation of providing some theoretical and practical references to the whole brain teaching of basketball techniques and tactics of middle school. In the experiment, it mainly gives comparative analysis to experimental group and control group from such aspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Literature [12] emphasized the importance of teamwork in sports teaching, concluded that the physical education model improved motor skills with the help of gamification, and verified the effect of the physical education model on team cohesion by teaching controlled experiments. Literature [13] provides a theoretical and practical reference study for wholebrain teaching in basketball, arguing the effectiveness of whole-brain teaching in basketball technical training based on a comparative analysis of skill tests and key skills such as body coordination. This paper firstly divides the fuzzy comprehensive evaluation model into single-factor fuzzy comprehensive evaluation and multilevel fuzzy comprehensive evaluation according to the different research factors of college students' basketball athletic ability and performance.…”
Section: Introductionmentioning
confidence: 99%
“…Literature [12] emphasized the importance of teamwork in sports teaching, concluded that the physical education model improved motor skills with the help of gamification, and verified the effect of the physical education model on team cohesion by teaching controlled experiments. Literature [13] provides a theoretical and practical reference study for wholebrain teaching in basketball, arguing the effectiveness of whole-brain teaching in basketball technical training based on a comparative analysis of skill tests and key skills such as body coordination. This paper firstly divides the fuzzy comprehensive evaluation model into single-factor fuzzy comprehensive evaluation and multilevel fuzzy comprehensive evaluation according to the different research factors of college students' basketball athletic ability and performance.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, for first-time spectators or people with visual and hearing disabilities, due to the confusion of the referee's gestures, it is easy to lose interest in watching the game and unable to feel the passion of basketball [7][8]. In professional leagues, such as the U.S. Men's Basketball League and the Chinese Men's Basketball League, clubs equip their teams with video analysts, who analyze the technical and tactical characteristics of players and referee's decisions in the game to improve the team's winning rate [9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Basketball training is about ways and means to increase tactical awareness training while improving the level of training, and basketball tactical training can improve the will to fight tenaciously and improve the tactical level and tactical awareness of basketball players [3][4][5].…”
Section: Introductionmentioning
confidence: 99%